2011
DOI: 10.1038/ijir.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between penile fracture and Peyronie's disease: a prospective study

Abstract: Peyronie's disease is postulated to be initiated by repetitive minor traumas to the fully or partially erect penis. We investigated Peyronie's disease prospectively in cases treated for penile fracture (PF) within the last 20 years. Medical records of 63 cases treated for PFs were reviewed. Subjects were required to self-assess their current penile morphologies and sexual functions. Penile nodules and Peyronie's plaques were also evaluated with physical examination, ultrasonography and magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…However, multiple studies in humans investigating the incidence of Peyronie's disease after penile fracture or in patients with a long history of forcefully bending the erect penis (taqaandan) did not show a correlation between trauma and Peyronie's disease 151,152 . This observation might suggest that several unknown genetic factors are involved in the development of Peyronie's disease.…”
Section: Nature Reviews | Urologymentioning
confidence: 99%
“…However, multiple studies in humans investigating the incidence of Peyronie's disease after penile fracture or in patients with a long history of forcefully bending the erect penis (taqaandan) did not show a correlation between trauma and Peyronie's disease 151,152 . This observation might suggest that several unknown genetic factors are involved in the development of Peyronie's disease.…”
Section: Nature Reviews | Urologymentioning
confidence: 99%
“…[1][2][3][4] The disease is postulated to be initiated by repetitive minor traumas to the fully or partially erect penis. 5 Main symptoms of the acute disease phase are increasing plaques and deviation, in combination with pain. 1 In the stable phase of PD, which usually begins 12 months from onset, deviation and plaques remain stable while deviation is the main symptom.…”
Section: Introductionmentioning
confidence: 99%
“…This method only led to the formation of the acute inflammatory response and the tissue structure returned to normal after the acute phase. Acikgoz et al [29] and Zargooshi et al [30] also discovered that single trauma to penile albuginea would not lead to PD via prospective studies one after another. However, a latest meta-analysis has shown that penile fracture, a kind of penile trauma, could result in ED, penile plaques and curvature, though the incidence of these complications was only approximately 13% [31].…”
Section: Discussionmentioning
confidence: 99%